Population Aging and Decline Will Happen Sooner Than We Think - Jonathan R. Guillemot; Xue Zhang; Mildred E. Warner (Social Sciences, 2024)
The United Nations’ 2022 World Population Prospects suggests the global population will reach 10 billion people in 2058 and will peak in 2086. Aggregated data do not account for regional and age-group realities, which draw a more pressing picture. We analyze the World Population Prospects 2022 data according to age groups and regions and show that population peaks are going to occur sooner in some regions of the world than others, and the working-age population will peak on average 10 to 20 years before the overall population peaks. Africa is the only world region expected to continue to experience significant population growth. The population will be increasingly made up of larger proportions of older ages than younger, thereby shifting the dependency ratio. Reflections on the implications of an aging and shrinking population on policy regarding fertility, aging, migration, urban planning and economic development are needed. The challenge is not to be left for future generations to face; it is happening tomorrow.